Polycystic ovary syndrome and cardiometabolic risks - Siusiuka, V. H.; Demidenko, O. V.; Serhienko, M. Yu.; Deinichenko, O. V.; Onopchenko, S. P.; Сюсюка, Володимир Григорович; Деміденко, Олександр Вікторович; Сергієнко, Марина Юріївна; Дейніченко, Олена Валеріївна; Онопченко, Світлана Павлівна (My University, 2023)
Cardiovascular disease (CVD) is the main Cause of Death in the world, causing about 15.2 million deaths per year, according to the World Health Organization (WHO). This is the same for both men and women, even in some developed countries more women than men die from CVD.
Keywords: тези доповідей